Japanese subgingival microbiota in health vs disease and their roles in predicted functions associated with periodontitis - Ikeda, Eri; Shiba, Takahiko; Ikeda, Yuichi; Suda, Wataru; Nakasato, Akinori; Takeuchi, Yasuo; Azuma, Miyuki; Hattori, Masahira; Izumi, Yuichi (Odontology, 2020)
The present study aimed to identify and compare the microbial signatures between periodontally healthy and periodontitis subjects using 454 sequences of 16S rRNA genes. Subgingival plaque samples were collected from ten periodontally healthy subjects and ten matched chronic periodontitis patients. Bacterial DNA was extracted and next-generation sequencing of 16S rRNA genes was performed. The microbial composition differed between healthy subjects and periodontitis patients at all phylogenetic levels. Particularly, 16 species, including Lautropia mirabilis and Neisseria subflava predominated in healthy subjects, whereas nine species, including Porphyromonas gingivalis and Filifactor alocis predominated in periodontitis. UniFrac, a principal coordinate and network analysis, confirmed distinct community profiles in healthy subjects and periodontitis patients. Using predicted function profiling, pathways involved in phenylpropanoid, GPI-anchor biosynthesis, and metabolism of alanine, arginine, aspartate, butanoate, cyanoamino acid, fatty acid, glutamate, methane, proline, and vitamin B6 were significantly over-represented in periodontitis patients. These results highlight the oral microbiota alterations in microbial composition in periodontitis and suggest the genes and metabolic pathways associated with health and periodontitis. Our findings help to further elucidate microbial composition and interactions in health and periodontitis.